Hubungan Dukungan Emosional Orang Tua dengan Kemandirian Anak di Jorong Ranah Panantian Kabupaten Pasaman Barat - Sunarti, Vevi; Nabilla, Annisa Suci (Universitas Negeri Padang, 2024)
The Relationship Between Family Social Support and Children's Independence in Jorong Ranah Panantian, West Pasaman Regency. Thesis. Faculty of Science Education. Padang State University. The background of this research is the low level of independence of children in Jorong Ranah Panantian, West Pasaman Regency. This research aims to look at the picture of family social support, the picture of children's independence and the relationship between family social support and children's independence in Jorong Ranah Panantian, West Pasaman Regency. This research uses a quantitative approach with a correlational type of research. The population of this study consisted of 35 children with an age range of 10 to 12 years. Meanwhile, the sample for this study consisted of 28 children, taken using a simple random sampling technique. The data collection technique uses a questionnaire. Then, for the data analysis technique, the Spearmen rho formula is used. The results of the research show that family social support is still low, children's independence in Jorong Ranah Panantian is still low, there is a significant relationship between family social support and children's independence in Jorong Ranah Panantian, West Pasaman Regency. Recommended for families.